Academic co-creation: development and validation of a short scale - Ventura-León, José; Sánchez-Villena, Andy Rick; Caycho-Rodríguez, Tomás; White, Michael (Frontiers in Education, 2023)
Introduction Given the profound changes caused in higher education by the COVID-19 pandemic, affecting 1.6 billion students and 63 million educators globally, there arises the necessity for quantifiable measures that capture the essence of academic co-creation. This study aimed to develop and validate a short scale that measures academic co-creation (AC-S) in a sample of higher education students. Methods A total of 3,169 students from three Peruvian cities participated in the study (Mean Age = 25.77 years old; SD = 8.92 years); 1889 were female (59.60%) and 1,280 (40.40%) males. Qualitative and quantitative procedures were used for test construction. Item response theory (IRT) under the two-parameter graded response model (GRM-2PL) and test information function were used to examine reliability; additionally, a brief measure of academic satisfaction was used to provide evidence of relationship with another variable. Results The AC-S displayed strong fit and reliability, assessed through the test information function and standard error. It also showed a moderate correlation with academic satisfaction, bolstering its validity by linking with a pertinent variable. Its brevity enhances its practicality for education and research, efficiently fitting explanatory models and educational contexts. Despite substantial sample size and advanced psychometric methods, the study acknowledges limitations in sample representativeness and cross-sectional design. In conclusion, IRT and SEM techniques compellingly support the AC-S’s reliability and validity. Conclusion The scale’s one-dimensionality, local independence, reliability, and academic satisfaction relationship form a foundation for future exploration of co-creation-based educational models. Further studies should evaluate its performance across diverse cultural contexts.